A Perturbation Approach to the Study of Unsteady MHD Periodic Flow of Viscous Fluid through a Planer Channel (International Journal of Food and Nutritional Sciences, 2022)
In this investigation, we study the periodic unsteady flow of a viscous incompressible fluid through a porous planer channel in the presence of a transverse magnetic field. Through the use of perturbation techniques, the governing equations are solved. The induced magnetic field are negligible. The fluid's velocity profiles can be computed analytically and given as expressions. Tables gives an overview of the computations that went into the response. With the aid of graphs and figures, the impacts of different parameters on the flow field are examined. Based to the findings, the flow field has been significantly affected by the transverse magnetic field's presence and its perturbation. When a magnetic field is present, it is discovered that the velocity profiles are not uniform and the flow is more unstable. In the presence of a magnetic field, it is discovered that the velocity profiles are not uniform and the flow is more unstable. There is additional discussion of the impacts of several parameters, including the Reynolds number, the strength of the magnetic field, and the perturbation parameter.